Analysis of blanching and drying temperature on the physical characteristics of breadfruit chips during drying - Ahmad, Ilham; Jassin, Ernawati; Muhtar, Imran (Talenta Publisher, 2025)
This study evaluated how blanching regime and drying temperature influence moisture removal dynamics and dimensional changes in breadfruit chips. We dried breadfruit chips at 55 or 65 °C following one of three pretreatments: blanching at 40 °C for 15 min, blanching at 80 °C for 30 min, or no blanching. Raising drying temperature lowered the equilibrium moisture content (EMC) and shortened the time to reach it: at 55 °C, EMC stabilized at 6.94–17.03% after 840–1290 min; at 65 °C, EMC was 4.33–14.57% after 810–1050 min. Across both temperatures, mild blanching (40 °C, 15 min) consistently produced the highest drying rate, whereas no blanching or severe blanching (80 °C, 30 min) yielded the lowest rates. Shrinkage showed a similar tendency: at 55 °C, it was greatest after mild blanching and lowest after severe blanching; at 65 °C, it remained greatest with mild blanching but was lowest without blanching. These patterns suggest that mild blanching may open cellular pathways, enhancing water diffusion and promoting structural collapse, whereas harsher conditions or no blanching restrict mass transfer and limit shrinkage. Overall, elevating the temperature accelerated drying and reduced EMC, and blanching conditions strongly modulated both drying rate and product dimensions. From a processing standpoint, pretreatments should be selected to balance throughput with textural quality; for applications prioritizing rapid dehydration, mild blanching at 40 °C for 15 min is advantageous, whereas minimizing shrinkage may require either higher-temperature drying without blanching or carefully optimized, shorter blanching steps.